(untitled) (International Journal of Food and Nutritional Sciences, 2022)
India has always been known for its knowledge tradition and knowledge culture. Indian Knowledge Tradition has an influential and rich history since the ancient age. It has its own characteristics, its place of learning, its texts, and their classifications. In this knowledge tradition in ancient India knowledge was based on the Vedas and other Dharmashastras. Though it was famous for its disciplined education and great knowledge of all areas, it had some discrepancies. In ancient India, the knowledge system was based on caste hierarchies. Only the students from three upper castes like Brahmins, Kshatriyas, and Vaishyas had the right to enter the schools and take education. They were dvijas (twice-born) and had the right to Upanayana, the initiating ceremony of schooling. The Shudras were not permitted to attain Upanayana because they were not twice-born. They had no right to enter the schools or to read and recite the Vedas. The Shudras were oppressed, marginalized ’subalterns’ and were living the lives of subordinates under the domination of higher castes. Although the term subaltern became regular with the emergence of ’Subaltern Studies’ in the decade of 1980s, the subalterns have been in existence since the beginning of human history. The Shudras were subalterns in ancient India and hadbeen kept away from education and knowledge. So it is needed to focus on the injustice done to the subaltern Shudras in the Indian education system and knowledge in ancient India.